Analisis Deterministik Kausal Secara Sosial yang Menyebabkan Pertanggungjawaban Pidana di Era 4.0 - Muhamad Ghofir Makturidi; Ayi Yunus Rusyana; Hisam Ahyani (PAMALI: Pattimura Magister Law Review, 2022)
Introduction: Crime and punishment in the 4.0 era are 1) a behavior, 2) a type of social phenomenon in interactions that are built between humans, 3) natural and social phenomena, 4) including interactions between people in social life, 5) considered as a process deterministic mechanics based on the law of causality. So that nowadays the study of crime and punishment in the 4.0 era needs to be developed in order to realize national development.Purposes of the Research:  To uncover and explore deterministics based on the law of causality, which causes criminal liability in Era 4.0, which needs to be developed in order to realize national development.Methods of the Research: This research method is a normative research where causal deterministics in era 4.0 are aimed at sentencing and are not only based on the concept of retributive justice alone, but also on the principle of benefits generated in the sense of aiming to prevent the recurrence of similar crimes and thereby create order and national security.Results of the Research: I that crime and punishment against socially causal deterministic challenges that lead to criminal responsibility in the 4.0 era is a necessity as Satjipto Rahardjo revealed that the law always develops following human development and following the needs and values that live in humans to realize social justice for all citizens Indonesia, especially for society 5.0, especially in terms of digitalization through modern law as a new and renewable breakthrough and making changes to the legal paradigm according to the demands of the times.